Large-area, periodic, and tunable intrinsic pseudo-magnetic fields in low-angle twisted bilayer graphene - Haohao Shi (Nature Portfolio, 2020)
Precisely strained graphene layers can enable observation of periodic pseudo-magnetic fields with high symmetry. Here, the authors report experimental tuning of large area periodic pseudo-magnetic fields within twisted bilayer graphene and massive Dirac electrons having circularly localized pseudo-Landau levels.